Performance evaluation of a distributed SFBC relay-assisted scheme for OFDM systems - Teodoro, Sara
In this paper we investigate the performance of a 2-relay cooperative scheme, where all the nodes are equipped with a single antenna. We consider Decode-and-Forward as relaying protocol and a distributed space-frequency block is employed. Two schemes are proposed: one with and another without the direct path available. Signals expressions are derived under various propagation scenarios, considering power constraint imposed on cooperating nodes. The aim of this work is to evaluate the proposed relay-assisted schemes, under realistic situations (e.g. correlated antennas, precise channel models, Doppler effects) for typical pedestrian scenarios based in WiMax specifications and using channel turbo coding. The coded performance of the proposed relay-assisted schemes is evaluated, considering different modulations, and compared against non-cooperative OFDM based systems. The proposed cooperative scheme outperforms in most of the studied scenarios the SISO and the co-located 2x1 SFBC. Copyright © 2010 The authors.